IMF Staff papers : Volume 33 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1986)
This paper begins by describing the basic concepts of Islamic banking, focusing on the issue of elimination of the rate of interest from the system. Islam expressly prohibits a fixed or predetermined return on financial transactions but allows uncertain rates of return deriving from risk-taking activities. Consequently, a banking structure in which the return for the use of money fluctuates according to actual profits made from such use would be consistent with the precepts of Islam. The paper concludes that from an economic standpoint the principal difference between the Islamic and the traditional banking systems is not that one allows interest payments and the other does not. The more relevant distinction is that the Islamic system treats deposits as shares and accordingly does not guarantee their nominal value, whereas in the traditional system such deposits are guaranteed either by the banks or by the government.